Maghemite nanorods anchored on a 3D nitrogen-doped carbon nanotubes substrate as scalable direct electrode for water oxidation. (5th January 2016) - Sharifi, Tiva; Kwong, Wai Ling; Berends, Hans-Martin; Larsen, Christian; Messinger, Johannes; Wågberg, Thomas
Abstract: A hybrid catalyst 3D electrode for electrochemical water oxidation to molecular oxygen is presented. The electrode comprises needle shaped maghemite nanorods firmly anchored to nitrogen doped carbon nanotubes, which in turn are grown on a conducting carbon paper that acts as efficient current collector. In 0.1 M KOH this hybrid electrode reaches a current density of 1 mA/cm 2 (geometric surface) at an overpotential of 362 mV performing high chronoamperometric stability. The electrochemical attributes point toward efficient catalytic processes at the surface of the maghemite nanorods, and demonstrate a very high surface area of the 3D electrode, as well as a firm anchoring of each active component enabling an efficient charge transport from the surface of the maghemite rods to the carbon paper current collector. The latter property also explains the good stability of our hybrid electrode compared to transition metal oxides deposited on conducting support such as fluorine doped tin oxide. These results introduce maghemite as efficient, stable and earth abundant oxygen evolution reaction catalyst, and provide insight into key issues for obtaining practical electrodes for oxygen evolution reaction, which are compatible with large scale production processes. Highlights: Hierarchical self-assembled carbon based structures with unique 'tree-like' morphology are used as catalyst support. The defective walls of N-doped CNTs provide favorable sites to grow maghemite nanorods. The hybrid catalyst show excellent ability for the oxygen evolution reaction with an overpotential of 362 mV @ 1 mA/cm 2 . The firm anchoring of the active components to the support gives very good stability.